Aplicación de un Sistema Robusto al Control de Posición de un Cilindro Neumático, expuesto a perturbaciones. (2011)
In industrial applications, the processes are very complex, with delays, disturbances and non-linear behavior, an this is the case for pneumatic systems. Though the conventional controllers can be adjusted to correct these changes, the transients from the disturbances can be extremely unfavorable for the actuators involved in the system. This is the reason why an advanced control technique (Robust) has been proposed and applied to the mathematical model of a position control system of a pneumatic cylinder exposed to disturbances, in order to verify numerically the controller’s performance. This paper shows the results obtained by applying the robust control system, after performing the analysis of step response in transient and steady state, before and after including the controller. For this, six tests were conducted with six controllers by using the technique Hinfinity (H∞) , and the results showed that the dynamic conditions in the system were enhanced.